Представьте в виде многочлена выражение: 1) (с-2)(с+2) 5) (х+7)(х-7) 2) (12-х)(12+х) 6) (5а-8b)(5a+8b) 3) (3х+у)(3х-у 7) (8m+2)(2-8m) 4) (6х-9)(6х+9 8) (13c-14d)(14d+13c) заранее за ответы)

trol77 trol77    2   16.08.2019 13:40    0

Ответы
Оля2204202 Оля2204202  20.08.2020 09:48

Объяснение:

1)

(c-2)(c+2) = c^{2} -4;

2)

(12-x)(12+x)= 144-x^{2} ;

3)

(3x+y)(3x-y)=9x^{2} -y^{2} ;

4)

(6x-9) (6x+9)= 36x^{2} -81;

5)

(x+7)(x-7) =x^{2} -49;

6)

(5a-8b)(5a+8b)= 25a^{2} - 64b^{2} ;

7)

(8m+2)(2-8m)= 4-64m^{2} ;

8)

(13c-14d) (14d+13c) =169c^{2} -196d^{2}.

ПОКАЗАТЬ ОТВЕТЫ